An Investigation of Zoonotic Bacterial Pathogens Associated with Rodents in Rural Areas of Nellore, India: Life Sciences -Biotechnology - B. Vadela, Manohar; Karri, Satyanagalakshmi; Thathapudi, Daveedu; Bogireddy, Devi; Gundi, Vijay A.K.B. (International Journal of Life Science and Pharma Research, 2023)
Rodent species are known to harbour and host various zoonotic pathogens, including bacterial, viral, fungal, and protozoal species. Several investigations proved that commensal rats (Rattus spp.) are potential to transmit drug-resistant and hyper-virulent bacterial pathogens to humans. India’s rapid urbanization and developmental activities facilitated rats to live near the human population. However, few information was known about bacterial species associated with rodents and their role in zoonotic risk to humans in India. The present study aimed to (i) investigate the presence of bacterial pathogens associated with rodents and (ii) infer the prevalence and diversity of potential bacterial pathogens in Nellore district, India. Bacterial prevalence was determined by isolation and identification techniques. The isolated bacterial cultures were submitted for phenotypic observation, biochemical identification using the VITEK 2 compact automated system, and molecular detection by DNA extraction and amplification of the 16S rRNA gene. A diversified bacterial community belonging to 14 species was detected from all collected animals. Bacterial species’ prevalence was comparatively higher in black rats (n=66) than brown rats (n=27). 46 rats out of 93 were found to be positive (49.4%) for bacterial presence. A significant variation was found in the prevalence of bacterial species between both rodent species. The highest bacterial prevalence was recorded for Bacillus spp. (36%) followed by E. coli (29%). The prevalence of Klebsiella pneumoniae was found as 17%, of which 18% in black rats and 14% in brown rats. Listeria spp.’s prevalence was 23.6%, but a higher prevalence was observed in black rats (25.7%). Surprisingly, an uncommon pathogen, Sphingomonas paucimobilis, was detected in both rodent species. These results suggest that Rattus rats in Nellore were suspected to be potential carriers of transmitting zoonotic bacterial species to humans.